Clinical relevance of asymptomatic intracerebral hemorrhage post thrombectomy depends on angiographic collateral score. Issue 8 (August 2020) - Nawabi, Jawed; Kniep, Helge; Broocks, Gabriel; Faizy, Tobias D; Schön, Gerhard; Thomalla, G; Fiehler, Jens; Hanning, Uta
Asymptomatic intracerebral hemorrhage (aICH) is a common phenomenon in patients with acute ischemic stroke (AIS) treated with endovascular thrombectomy (ET). However, the impact of aICH on the functional outcome remains widely unclear. In this study, we aimed at identifying predictors for aICH and analyzing its impact on functional outcome. Patients with AIS due to large artery occlusion in the anterior circulation treated with successful ET were enrolled in a tertiary stroke center. Patients with aICH or without intracerebral hemorrhage were included according to post-treatment CT performed within 72 h; 100 consecutive patients fulfilled the inclusion criteria and 30% classified with aICH. In logistic regression analysis, lower collateral score (OR 0.24; 95% CI 0.12–0.46, p  < 0.0001) was significantly associated with aICH. Less patients with aICH achieved an independent outcome (mRS 0–2, 16.7% vs. 44.3%, p  = 0.007). Poor outcome (mRS 4–6) was significantly higher in patients with aICH (41.4% vs. 70%, p  = 0.021). Patients with aICH had a lower ratio of independent outcome (OR 0.23, 95% CI 0.05–0.1.05, p  = 0.041) than without ICH. There were no differences concerning poor outcome ( p  = 0.5). Lower collateral status was a strong independent predictor for aICH. aICH after successful ET may decrease the likelihood of an independent functional outcome without influencing poor outcome.